2022
DOI: 10.3390/children9050733
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Masks in Neonatal Resuscitation—A Narrative Review of Updates 2022

Abstract: Positive pressure ventilation (PPV) is crucial to neonatal cardiopulmonary resuscitation because respiratory failure precedes cardiac failure in newborns affected by perinatal asphyxia. Prolonged ineffective PPV could lead to a need for advanced resuscitation such as intubation, chest compression, and epinephrine. Every 30 s delay in initiation of PPV increased the risk of death or morbidity by 16%. The most effective interface for providing PPV in the early phases of resuscitation is still unclear. Laryngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“… 2 Leakage around the mask is one of the main problems related to its use, with losses of 50–70% of the delivered flow. 8 , 17 This leak is not always perceived by the professionals, causing insufficient delivery of tidal volume and compromising the success of PPV. 18 , 19 The application of the mask to the face of the newborn can also trigger the trigeminal-cardiac reflex, with consequent stimulation of the brainstem nuclei, causing apnea, bradycardia, and hypotension through reflex vagal action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Leakage around the mask is one of the main problems related to its use, with losses of 50–70% of the delivered flow. 8 , 17 This leak is not always perceived by the professionals, causing insufficient delivery of tidal volume and compromising the success of PPV. 18 , 19 The application of the mask to the face of the newborn can also trigger the trigeminal-cardiac reflex, with consequent stimulation of the brainstem nuclei, causing apnea, bradycardia, and hypotension through reflex vagal action.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LMA is associated with a higher success rate in neonatal resuscitation 6 and shorter ventilation time 7 than the use of FM. Furthermore, LMA is less invasive, requires less training, and is more prone to success on the first insertion attempt 8 than tracheal intubation. A meta-analysis comparing LMA with FM concluded that LMA was more effective than FM because of the following reasons: need for intubation, time to spontaneous breathing, ventilation time, Apgar scores, and admission to the neonatal intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…The laryngeal mask airway (LMA) is considered an alternative device for resuscitation in infants above 34 weeks gestational age (GA) by the Neonatal Resuscitation Program (NRP) and the International Liaison Committee on Resuscitation 1 . While LMAs in the pediatric population have been predominantly studied in surgeries lasting 1–3 h, 1 there are reports describing prolonged use of LMAs in neonates without sequelae 2,3 . Pharyngeal mucosal damage due to LMA use is influenced by pressure exerted over tissue, cuff inflation, and duration of use.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation underscores the importance of rigo rous research and exploration. 3) In addition, gastric insufflation warrants further investigation. Although second-generation LMs offer potential solutions, ongoing examinations are required.…”
mentioning
confidence: 99%
“…In contrast, the i-gel size 1 was designed for infants weighing 2-5 kg. 3) Clinical trials involving the LMA Supreme for neonatal resuscitation included infants with birth weights as low as 1.5 kg. 11) Moreover, there are reports of successful LM usage in an 800-g newborn, indicating a widening scope.…”
mentioning
confidence: 99%